Sanksi Adat Perkawinan Semarga Masyarakat Batak Angkola Di Kecamatan Batang Angkola Kabupaten Tapanuli Selatan - Dini Suryani; Ageng Triganda Sayuti (Zaaken: Journal of Civil and Business Law, 2022)
This study aims to determine and analyze the customary sanctions for the same clan  marriage of the Angkola Batak Community in Batang Angkola District, South Tapanuli Regency and the factors causing the non-implementation of the customary sanction of the same clan marriage of the Angkola Batak community in Batang Angkola District, South Tapanuli Regency. The problem to be researched is how to implement the customary sanction of the same clan marriage of the Angkola Batak community in Batang Angkola District, South Tapanuli Regency? And the factors causing the non-implementation of customary sanctions for same clan marriage in Batang Angkola District, South Tapanuli Regency? This research method is empirical juridical. The research location is in Batang Angkola District, South Tapanuli Regency. The results of this study are the implementation of customary sanctions for clan marriages of the Angkola Batak community in Batang Angkola District, South Tapanuli Regency, not carried out according to applicable regulations. The factors causing the non-implementation of customary sanctions are religious factors, love factors, economic factors, educational factors and modernization factors. Keywords: Adat Sanctions, The same clan marriage, Angkola Batak Abstrak Penelitian ini bertujuan untuk mengetahui dan menganalisis Sanksi Adat Perkawinan Semarga Masyarakat Batak Angkola Di Kecamatan Batang Angkola Kabupaten Tapanuli Selatan dan Faktor-faktor penyebab tidak terlaksananya sanksi adat perkawinan semarga masyarakat batak angkola di Kecamatan Batang Angkola Kabupaten Tapanuli Selatan. Permasalahan yang akan diteliti adalah bagaimana pelaksanaan sanksi adat perkawinan semarga masyarakat batak angkola di Kecamatan Batang Angkola Kabupaten Tapanuli Selatan? Dan faktor-faktor penyebab tidak terlaksananya sanksi adat perkawinan semarga di Kecamatan Batang Angkola Kabupaten Tapanuli Selatan? Metode penelitian ini adalah yuridis empiris. Lokasi penelitian yaitu di Kecamatan Batang Angkola Kabupaten Tapanuli Selatan. Hasil penelitian ini adalah Pelaksanaan Sanksi Adat Perkawinan Semarga Masyarakat Batak Angkola di Kecamatan Batang Angkola Kabupaten Tapanuli Selatan tidak terlaksana sesuai aturan yang berlaku. Faktor penyebab tidak terlaksananya sanksi adat tersebut karena faktor agama, faktor cinta, faktor ekonomi, faktor pendidikan dan faktor modernisasi.